Analysis of The Level of Vulnerability to Landslide Disaster in Pamijahan District of Bogor Regency - Dwi Ramadhan; Siti Dahlia (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2023)
The Pamijahan District area is a plain that is quite vulnerable to landslides. The morphology is hilly and has a slope that varies from gentle (8–15%) to steep (> 40%). In addition, landslides can be very risky due to social, economic, physical, and environmental conditions. The purpose of this study was to determine the level of vulnerability to landslides and the distribution of vulnerability to landslides in Pamijahan District. In this study, the methodology and techniques used are quantitative descriptive with scoring or grading data analysis techniques. Based on the analytical calculations carried out, there are two categories of landslide vulnerability levels, namely high vulnerability and moderate vulnerability. The high vulnerability category covers an area of 2,605 ha covering 6 villages namely Ciasihan Village, Cibitung Kulon Village, Gunung Sari Village, Gunung Picung Village, Gunung Menyan Village, and Gunung Bunder Satu Village. The moderate vulnerability category covers an area of 3,959 ha covering 4 villages namely Cibunian Village, Ciasihan Village, Purwabakti Village, and Pasarean Village.